The Influence of Organizational Climate, Situational Leadership Style, and Job Satisfaction on Employee Performance at the East Kalimantan Regional Police Medical and Health Unit (Biddokes) - Ayati, Syari; Sitaniapessy, Arthur; Widokarti, Joko Rizkie (Paradoks : Jurnal Ilmu Ekonomi, 2025)
In a complex work environment such as Biddokes, a deep understanding of factors like Organizational Climate, Situational Leadership Style, and Job Satisfaction is crucial to ensure optimal employee performance. Organizational climate reflects the culture, norms, and values governing organizational behavior, influencing employee motivation, engagement, and job satisfaction. On the other hand, the situational leadership style emphasizes leaders' flexibility in adjusting their leadership approach according to the needs and readiness of subordinates, which can affect motivation, productivity, and team performance. Meanwhile, Job Satisfaction reflects employees' subjective evaluation of the work environment, including the alignment between individual needs and the workplace environment, which can influence motivation, commitment, and employee retention. This study uses a quantitative research approach. Survey methods and questionnaires were employed to collect data from respondents at the East Kalimantan Regional Police Medical and Health Unit (Biddokes). Multiple regression statistical analysis was used to examine the relationship between independent variables (Organizational Climate, Situational Leadership Style, and Job Satisfaction) and the dependent variable (Employee Performance). Based on the results of the analysis, it can be concluded that factors such as organizational climate, situational leadership style, and job satisfaction significantly impact employee performance at Biddokes Polda Kalimantan Timur. A positive organizational climate, including effective communication, professional relationships, and interdepartmental cooperation, can enhance employee performance. A flexible and adaptive situational leadership style allows leaders to motivate and guide subordinates according to their needs and readiness, contributing to better performance. Additionally, employee job satisfaction, influenced by various factors such as salary, promotion opportunities, relationships with coworkers, and job responsibilities, directly impacts employee performance. Therefore, Biddokes Polda Kalimantan Timur management should pay attention to and improve these aspects to enhance productivity, efficiency, and service quality.